Associação entre acuidade tátil, dor, funcionalidade e síndrome da sensibilização central em indivíduos com e sem cervicalgia crônica: um estudo transversal - Ferreira, Cheila de Sousa Bacelar (2020)
The study aimed to verify the correlation between tactile acuity, intensity of pain at rest and movement, functional capacity, catastrophization and symptoms of central sensitization syndrome in individuals diagnosed with chronic neck pain. Thus, a cross-sectional study was carried out in accordance with the STROBE Statement. a physical therapist was in charge of recruiting, diagnosing and allocating volunteers into two groups: cervical pain group and control group. Another physical therapist was in charge of administering the assessments. A third researcher processed and analyzed the data. All researchers were familiar with the assessment procedures, having an average of five years of training in Physiotherapy. In sequence, the evaluations were carried out: evaluation form, numerical pain scale, neck disability index, catastrophic thoughts about pain scale, central sensitization inventory and assessment of tactile sensitivity. All assessments were carried out individually, in a private room and with no time limit for completion. The study was composed of two distinct groups: individuals with chronic neck pain (n = 46) and without neck pain (n = 39). The groups did not show significant differences (p> 0.05) in demographic characteristics. With regard to TDDP, it was observed that individuals with pain presented alterations in tactile discrimination, with a significant and clinical increase in perceived distance (MD = 5.45, 95% CI 4.42 to 6.47; Cohen d = 2.34, 95% CI = 1.78 to 2.90) when compared to the control group. A positive, moderate and significant correlation was observed between TDDP and END at rest and movement, NDI and EPCD (r = 0.503 to 0.699, p <0.05), so that the greater the intensity of pain, disability and catastrophization, the smaller the perceived distance in the TDDP. In conclusion, our data suggest that tactile acuity is associated with clinical signs, pain intensity at rest and movement, cervical functionality and pain catastrophization. However, it is not related to symptoms of central sensitization syndrome in individuals diagnosed with chronic neck pain.